The Libechov minipig as a large animal model for preclinical research in Huntington's disease – thoughts and perspectives - Schramke, S; Schubert, R; Frank, F; Wirsig, M; Fels, M; Kemper, N; Schuldenzucker, V; Reilmann, R (Česká a slovenská neurologie a neurochirurgie, 2015)
Large animal models to explore the safety and tolerability of novel therapeutic approaches for Huntington's disease (HD) are in exploration to achieve higher translational reliability in future studies. Recently, a Libechov minipig has been established as one new transgenic (Tg) large animal model for HD. We here discuss the advantages and limitations in using this model in HD with regards to breeding, housing, handling, and with respect to homology to humans and ethical considerations. A group of TgHD and wild type (WT) female minipigs (n = 36) was used to gain first evidence about abovementioned aspects. It is concluded that Libechov minipigs may fulfill an important role to bridge the gap between rodents and non‑human primates in the translation to humans.
Keywords: Animals; geneticky modifikovaná zvířata; preklinické hodnocení léčiv; Huntington Disease; Models, Animal; chov; Huntingtonova nemoc; prasata; Drug Evaluation, Preclinical; zvířata; Ethics, Research; sekvenční homologie; velikost orgánu; Swine, Miniature; Animal Experimentation; mozek; Swine; Time Factors; časové faktory; Organ Size; etika výzkumu; experimenty na zvířatech; Brain; modely u zvířat; Housing, Animal; Breeding; bydlení zvířat; Animals, Genetically Modified; Sequence Homology; miniaturní prasata